Enhanced production rate of probiotic Enterococcus faecium A028 by repeated batch solid-state fermentation and its survival under hot air drying with cell-protective agents - Kannika A. (2023)
Probiotic viability is an important aspect of animal feed additives. Enterococcus faecium A028, a potential probiotic, was isolated from the intestinal digestion track of chicken. Production rate of E. faecium A028 probiotic inoculum with high total viable cell count (TVC) was enhanced using repeated batch solid-state fermentation (RB-SSF). The probiotic strain grew well in soybean meal (SBM) with average TVC of over 9 LogCFU/g in all RB-SSF experiments. Average specific growth rate of E. faecium A028 in fermented SBM (FSBM) was 50% repeated batch ratio (RB ratio) for 0.37 h−1, and higher than the batch process (0.33 h−1). Probiotic inoculum production rate was enhanced by increasing the RB ratio. Highest total TVC production rate was 128.15 LogCFU/h at 90% RB ratio, while average TVC was 9.09 LogCFU/g. Total production of FSBM at 90% RB ratio was 1.6 times higher than batch fermentation. Different protective agents were investigated to increase the survival of E. faecium A028 during hot air drying. Maltodextrin (MTD) provided the highest survival rate at 83.9% during 24 h of drying. RB-SSF effectively enhanced the production rate of probiotic strain cultivation in SBM, while MTD acted as a cell-protective agent and maintained the survival of E. faecium A028 during thermal drying.